INTEGRASI-INTERKONEKSI AL-QUR’AN, SAINS, DAN PERADABAN: KONSEP, METODE DAN PROYEKSI - Wahyudin, Dedi; Nasikin, Moh (el-Umdah, 2022)
After two decades of existence, the idea of an integrated-interconnected paradigm of science needs a comprehensive review to strengthen its organic relation with al-Qur'an and widen its horizon to cover civilizational dimensions that impact widely to humanity. Using the library research method and integrative-pragmatic paradigm of Islamic studies as proposed by Moroccan philosopher, Taha Abdurrahman, this article is aiming at describing the concept, method, and projection of integration and interconnection between al-Qur'an, science, and civilization. Scientific findings and results of the analysis show that al-Qur'an in its several verses has been spreading ontological codes of universe and formulas of civilization as keywords for both of them to make scientific exploration and historical movement to honor the human being. Qur'anic ways to reach such goals are educating qualified scientists with knowledge, faith, and good action; making science as a starting point to explain al-Qur'an in universal kind of language; and making civilizational formulas of al-Qur'an as the basis of historical movement. The projection of the integration and interconnection is manifested in harmonic relation between science achievements and the maturity of civilization, something necessarily required by the idea of planetary civilization that is projected to emerge at the end of this century